An investigation of Preschool Children's Family Functions: A General Outlook on the Family from the Mother's Perspective - (:unkn) unknown (EDAM, 2007)
This study aims to investigate preschool children's family functions. To fulfill this aim, mothers' viewpoints and characteristics (e,g;, educational level, age, number of children, time spent in Istanbul, relations With spouse, employment status, relatives living in the same house, and perceived economic level) have been considered. The study sample consists of the mothers (n = 897) of 416 girls and 481 boys aged 5 years old (60-72 months) attending 16 preschools in Istanbul. The findings show chat less healthy family functions are displayed by young mothers than older ones; primary school graduate mothers than more educated ones; mothers with three children than those with fewer children; mothers who have lived in Istanbul for 20-29 year.,; than those who have lived longer; mothers who have other relatives living with them thin those who do nor; non-working mothers than working ones; and mothers who stated that they were satisfied and moderately satisfied with their jobs than those who stated they were very satisfied. Other noteworthy Findings are that the better cite mother perceives her relations with her spouse and the better the economic situation, the healthier the Family. The results also reveal that as the number of relatives living with the family increases, family functions become less healthy.
Keywords: Functional structure of family; mother; preschool children